Assessing the Impact of the October 2020 Capena Earthquake on the Lago Puzzo Sinkhole (San Martino Valley, Rome, Italy): Seismological, InSAR, and Geophysical Evidence of Possible Causal Relationships - R. De Ritis; G. Rotella; C. Tolomei; G. Calderoni; F. Marra; A. Argentieri; P. Vitali; M. Fabiani; M. Chiappini; C. Doglioni (Pure and Applied Geophysics, 2025)
In October 2020, a low-magnitude earthquake struck near the village of Capena, approximately 30 kilometers north of Rome. This seismic event was particularly remarkable due to its shallow hypocenter and the complete absence of aftershocks. Additionally, both during and after the event, residents reported hearing loud rumbling noises on multiple occasions in the village and surrounding rural areas. The earthquake's epicenter is located in a sinkhole-prone region intersected by major infrastructure, including a high-speed railway, high-voltage power lines, and a provincial road. Given these conditions, public authorities and regional Civil Protection agency closely monitored the area, prompting a comprehensive investigation. The study adopted an interdisciplinary approach to assess the stability of sinkhole-prone zones and identify any geological changes potentially triggered by the earthquake. A key focus of the research was the "Lago Puzzo," a well-documented example of multiphase, still active, sinkhole evolution within the San Martino Valley, alongside other similar extinct features in the area. The investigation integrated three primary methodologies: spectral analysis of seismic data to characterize the October 2020 event; remote sensing (SAR) using InSAR analysis to map ground displacement; geophysical surveys (ERT) to reveal subsurface structures. Although the study found no direct correlation between the earthquake and the evolution of Lago Puzzo, the results provide valuable insights into the current deformation state of the sinkhole and offer projections for its potential future development. Ultimately, this research represents a significant step forward in refining hazard assessment methods for the region.

The fate of murine hepatitis virus (MHV-3) after intravenous injection into susceptible mice - M. Piazza; G. Pane; F. Ritis (Archives of Virology, 1967)

Andamento di alcune modificazione enzimatiche dei tessuti (adenilpirofosfatasi, rodanese) nelle varie fasi della infezione sperimentale da virus dell'encefalomiocardite (EMC) - F. Ritis; M. Coltorti; G. Giusti; V. Villari (Archives of Virology, 1955)